The performance of business incubation in malaysia polytechnics entrepreneurship centre (MPEC) - Liew, Foong Ching (2017)
There has been an increased interest in business incubation programs due to the rapid growth of the business incubators in the developed and developing countries. Likewise, Malaysia has put forth the importance of entrepreneurship as the key driver to the nation economy development to achieve the Malaysia Vision 2020. In conjunction to this, Malaysia Polytechnics Entrepreneurship Centre (MPEC) was established to promote entrepreneurship to the Polytechnics students and business incubation program is one of the main program to realize their objectives. Therefore, 25 business incubators were established in the Polytechnics throughout Malaysia. However, there has been a lack of study towards the performance of business incubation program under the initiatives of the MPEC since its’ establishment in year 2012. Thus, the aim of this study was to understand the performance of the business incubation program. A conceptual framework of the measurement for the performance of the business incubation program was built and had identified seven key indicators as the measurement indicators. A qualitative method was used in this study through documents review and in-depth interviews with the MPEC manager and three selected incubator managers. The results provided support for the conceptual framework, with the emergence of other contributing factors towards the performance of the business incubation but those other factors being secondary to the measurement of the performance. An implication for business incubation program is that the systematic measurement indicators for business incubation performance can assist in decisions on the continuation, interruption or modification of incubator activities.